Regional Characteristics of Porosity and Permeability of Dahebian Syncline Coal and Its Application - Zhao, Fuping; Wei, Yuanlong (Frontiers in Earth Science, 2022)
In order to study the basic properties of coal seam thus to provide reference for coalbed methane (CBM) production, the porosity and permeability of coal from DH and WJZ regions of Dahebian syncline in Liupanshui Coalfield were systematically studied. The results shows that the porosity and permeability of coal samples in DH region are between 7.4%~10.1% and 0.01mD~0.04mD respectively. The permeability is obviously anisotropic, and it is distributed in a U-shape along bedding angle. The porosity and permeability in the WJZ region are between 12.4%~24.85% and 0.3mD-4.8mD, but the correlation of permeability and bedding angle is not obvious. There are many primary cracks in coal matrix of WJZ region, while the coal of DH region is relatively complete. As a result, the porosity and permeability of WJZ coal samples are much higher than that of DH coal samples. With the change of confining pressure, obvious change has taken place in the permeability of coal in the two regions. When the confining pressure decreases from 2MPa to 8MPa, the permeability loss rate of coal samples is close to 80%. The internal mechanism of the permeability loss is related to crack closure and plastic deformation caused by confining pressure. In contrast, the porosity and permeability of coal in WJZ region are much higher than those in DH region, which indicates that the permeability of the same coal seam in the same structural will have great differences and inhomogeneities. Therefore, the WJZ region is the preferred area, which can be included in the preferential exploitation plan of CBM. In addition, for the typical syncline gas reservoir in Liupanshui Coalfield, it is necessary to consider the block division according to the porosity and permeability indexes, and select the optimal block and give priority to development of CBM. Furthermore, we should pay attention to the difference and adaptability of CBM development in different regions.